Species and Conservation Status of Birds in the Rawa Tripa Peat Forest Area, Nagan Raya, Aceh - Hendrix Kusuma; Ikbal Maulana; Aida Fithri; Widya Sari; Zuriana Siregar; Ghina Kamilah; Nada Ariqah; Rahmawati Rahmawati; Khairul Munawir; Zulhilmi Zulhilmi; Munreza Anandita; Novrizal Akbar; Rayhannisa Rayhannisa; Rubama Rubama (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Peat ecosystems are one of the tropical ecosystems that have high ecological value because they play a role in carbon storage, hydrological regulation, and as a habitat for various fauna groups, including birds. Rawa Tripa, as part of the Leuser Ecosystem Area, is one of the most important peat landscapes in Aceh that faces anthropogenic pressures such as forest fragmentation and land use change. The lack of basic data on bird communities in this area hinders evidence-based conservation efforts. This study aims to inventory the bird species found in the Tripa Peat Forest and assess their conservation value in the context of habitat management. The survey was conducted from July 18 to 28, 2024, using the point count method on 10 observation transects. The results of the study recorded 16 bird species from 12 families, with the Pycnonotidae family being the most commonly found group. Several species with important conservation status were also identified, such as Leptoptilos javanicus (Near Threatened), Acridotheres javanicus (Vulnerable), and the presence of Rhyticeros undulatus (Vulnerable) and their nest, indicating the availability of large trees for nesting. Based on their feeding behavior, the birds of Rawa Tripa exhibit a diversity of ecological functions, ranging from insectivores and frugivores to raptors. These findings indicate that Rawa Tripa still has habitat quality that supports bird communities, even though threats such as hunting and land degradation remain. This study emphasizes the urgency of long-term monitoring and the need for conservation strategies that maintain vegetation structure and wetland sustainability in the Rawa Tripa area.